VD_FINDINFO HC / 2011 / 416 vom 21. Juli 2011 - VD Tribunal cantonal (2011)
PROTECTION DE L'UNION CONJUGALE, OBLIGATION D'ENTRETIEN, MODIFICATION DES CIRCONSTANCES | 176 al. 1 ch. 1 CC, 179 al. 1 CC, 308 al. 1 let. b CPC (CH)